2012
DOI: 10.3329/ptcb.v22i1.11261
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Can be a New Plant Growth Regulator for Hybrid Cymbidium Micropropagation

Abstract: Present authors investigated the effect of two biopolymer hyaluronic acid (HA9) and chitosan (Chitosan H), and N 6 -benzyladenine (BA) supplemented with modified MS on organogenesis in protocorm-like bodies (PLBs) of a Cymbidium cultivar. The percentages of PLB formation from cultures showed 100 % in all treatments except for control (82.7%), 0.1 mg/l HA9 (93.3%) and 10 mg/l Chitosan H (93.3%) treatments. Addition of 0.1 mg/l HA9 to culture medium was highly efficient for PLB multiplication. Both 10 mg/l HA9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…In this concern, Habiba et al (2014) found that HA at 1 mg l -1 produced the highest shoots per explant of Cymbidium dayanum and Dendrobium kingianum respectively. Whereas, Kaewjampa et al (2012) found that 0.1 mg l -1 HA on culture medium was highly potent in PLB (protocorm like bodies)multiplication. Results of Haque et al(2016) showed that BA at 0.1 mg l -1 combined with HA at 0.1 mg l -1 are the most effective concentration for PLB, shoot induction and maximum fresh weight of C.insigne.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this concern, Habiba et al (2014) found that HA at 1 mg l -1 produced the highest shoots per explant of Cymbidium dayanum and Dendrobium kingianum respectively. Whereas, Kaewjampa et al (2012) found that 0.1 mg l -1 HA on culture medium was highly potent in PLB (protocorm like bodies)multiplication. Results of Haque et al(2016) showed that BA at 0.1 mg l -1 combined with HA at 0.1 mg l -1 are the most effective concentration for PLB, shoot induction and maximum fresh weight of C.insigne.…”
Section: Resultsmentioning
confidence: 96%
“…In general, such this work on turmeric was not done before according to the available researchand previous studies were on the Orchid Cymbidium only. Another successful result has been obtained by Kaewjampa et al(2012)and Nahar et al(2011). They investigated the effect of two biopolymer HA and Chitosan H, and BA supplemented with modified MS on organogenesis in protocorm like bodies (PLBs) of a Cymbidium.…”
Section: Effects Of Ha Concentrations On Indirect Regeneration Of C mentioning
confidence: 99%
See 1 more Smart Citation
“…phoeniceum. Kandungan bahan aktif berupa IAA, IBA, dan NAA bekerja pada jaringan meristem akar sehingga membentuk sistem perakaran baru (Kaewjampa, et al 2013) (Santoso, et al 2008). Panjang setek yang baik untuk masing-masing jenis tanaman berbeda satu dengan yang lainnya.…”
Section: Pembahasanunclassified
“…HA suppresses disease in cucumber, tomato and pepper (Park et al, 2008) and has shown to have antioxidant activity. HA have of recent been suggested as important components of Cymbidium in vitro culture media (Nahar et al, 2011Nahar and Shimasaki, 2014;Kaewjampa et al, 2012). Therefore, the objective of this study was to investigate the effect of light quality and plant growth regulator on organogenesis of C. dayanum in vitro.…”
mentioning
confidence: 99%